2009
DOI: 10.1007/s00435-009-0087-7
|View full text |Cite
|
Sign up to set email alerts
|

Male reproductive system in the Italian newt Lissotriton italicus (Peracca 1898) (Amphibia, Urodela): ultrastructural and morphological study with description of spermiogenesis, spermatozoon and spermatophore

Abstract: The Wrst morphological and ultrastructural description of testis, WolYan duct, spermatophore, and spermatozoon of Lissotriton italicus is provided. The male reproductive system of this species consists of a pair of monolobed testes, fat bodies, eVerent ductules, paired WolYan duct, and the cloaca. The WolYan duct is pseudostratiWed, consisting of an epithelium composed of an alternation of ciliated cells and non-ciliated secretory cells, with scattered basal cells. Melanocytes are found in the basal lamina of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
5
1
Order By: Relevance
“…In contrast to squamates, the spermatozoa are arranged in spherical bundles with their heads pointing toward the center of the circle. This differs from previous descriptions of sperm bundle organization in salamanders in which the heads are all aligned (spermatophores) (Sperone et al 2009) chondrichthyans in which the sperm are aligned on a single plane with the heads directly facing one another (spermatozeugmata) (Moura et al 2011), but resembles sperm bundle organization in the Echidna, Tachyglossus aculeatus (Djakiew and Jones 1981). Although Djakiew and Jones (1981) did not describe the organization of the sperm bundles in the Echidna, our examination of their plates indicates that they resemble those of the Tuatara.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…In contrast to squamates, the spermatozoa are arranged in spherical bundles with their heads pointing toward the center of the circle. This differs from previous descriptions of sperm bundle organization in salamanders in which the heads are all aligned (spermatophores) (Sperone et al 2009) chondrichthyans in which the sperm are aligned on a single plane with the heads directly facing one another (spermatozeugmata) (Moura et al 2011), but resembles sperm bundle organization in the Echidna, Tachyglossus aculeatus (Djakiew and Jones 1981). Although Djakiew and Jones (1981) did not describe the organization of the sperm bundles in the Echidna, our examination of their plates indicates that they resemble those of the Tuatara.…”
Section: Discussioncontrasting
confidence: 98%
“…This differs from previous descriptions of sperm bundle organization in salamanders in which the heads are all aligned (spermatophores) (Sperone et al . ) or chondrichthyans in which the sperm are aligned on a single plane with the heads directly facing one another (spermatozeugmata) (Moura et al . ), but resembles sperm bundle organization in the Echidna, Tachyglossus aculeatus (Djakiew and Jones ).…”
Section: Discussionmentioning
confidence: 99%
“…29,30,55 The spermatozoa of salamanders posses undulating membrane. 51,54,55,56,57,58, Spermatozoa have a swirl arrangement inside the cyst, with their heads oriented in the same direction as observed in Lissotriton italicus 21 and Ambystoma dumerilii illustrated here (Figs. 8A,B).…”
Section: Spermatids and Spermatozoamentioning
confidence: 76%
“…The shortest spermatozoa were reported for Hynobius nebulosus with a length of 156 mm, whereas the longest with about a length of 1mm was observed in Necturus maculosus. 59 The lengths of spermatozoa were also measured in several species: Lissotriton italicus (360 mm), 21 Ambystoma mexicanum (444 mm), A. dumerilii (451 mm), 58 E. bislineata (459 mm), E. lucifuga (523 mm), Desmognathus wrighti (504 mm), D. aeneus (388 mm), Plethodon cinereus (507 mm), P. dorsalis (535 mm), and P. dunni (626 mm). 54 The biological significance of differences in the lengths of spermatozoa is unknown.…”
Section: Spermatids and Spermatozoamentioning
confidence: 99%
“…Considering the collecting ducts never come into contact with the Wolffian ducts (where sperm are stored) until immediately cranial to where the urogenital papillae insert into the urodaeum, it is possible that the secretion serves to activate sperm. Sperone et al (2009) reported that sperm removed from the Wolffian ducts are immotile, indicating possible support for the latter hypothesis. Histological sections through the cranial extremities of the cloaca of male Plethodon albagula during spermatophore formation revealed the mixing of sperm and secretions from the collecting ducts (unpublished data).…”
mentioning
confidence: 93%